Do leading indicators help to predict business cycle turning points in Germany? - Ulrich Fritsche; Vladimir Kouzine (Deutsches Institut für Wirtschaftsforschung (DIW), 2002)
Using a binary reference series based on the dating procedure of Artis, Kontolemis and Osborn (1997) different procedures for predicting turning points of the German business cycles were tested. Specifically, a probit model as proposed by Estrella and Mishkin (1997) as well as Markov-switching models were taken into consideration. The overall results indicate that the interest rate spread, the long-term interest rate as well as some monetary indicators and some survey indicators can help predicting turning points of the business cycle.
Keywords: C22; E32; C25; 330; Business cycle; leading indicators; probit model; McFadden's R2; Markov switching models; Konjunkturindikator; Konjunkturprognose; Prognoseverfahren; Schätzung; Deutschland